Vous êtes sur la page 1sur 5

Algebraic Expressions

By Muralee.V.
Expanding One Brackets
Removing the bracket in an algebraic expression.

Solution

a(b + c) = ab + ac
Always be careful when removing bracket of operators.

Expanding
two brackets
- Expanding
the brackets
involve
multiplication

of linear expression in two separate brackets


Example 2
Expand the following
a) (4m 3k) (5n g)
b) (x + y) 2
c) (x + y) (x - y)
1

(4m 3k) (5n g)

b)

(x + y)

= (x + y) (x + y)
3 4

= x 2 + xy + yx + y 2
= x 2 + xy + xy + y 2
= x 2 + 2xy + y 2
c)

4
2

= 4m 5n 4m g 3k 5n 3k
= 20mn 4mg -15kn + 3kg
= 20mn 4gm -15kn + 3gk
1 2

a)
(4mn
rs + 7) =
4mn + rs 7

+(a + b) = +a + b
+(a b) = +a b
+ (a b) = a b
(a + b) = a b
(a b) = a + b
(a b) = a + b

Solution
a)

Example 1
Simplify
a)
(4mn
rs + 7)

1 2

(x + y) (x - y) = (x + y) (x - y)
3 4

(-g)

= x 2 - xy + yx - y 2
= x 2 - xy + xy - y 2
=x2 +y2
Tips
1. (x + y) 2

= x 2 + 2xy + y

2. (x - y) 2

= x 2 - 2xy + y 2

Factorisation
1. Factors = numbers or terms which can divide a term exactly.
2. State the term as a product of two different terms to find the factors of that term.
Example :
3ab = 1 3ab
= 3 ab
= a 3b
= b 3a
Therefore, the factors for 3ab are 1, 3, a, b, 3a, 3b, ab, 3ab
3. Factorisation of algebraic expression is the reverse of expansion
Expansion
Example : 3m(m + 9)

Factorisation

3m 2 + 27m

Example 3
Factorise each of the following
a)
r 2 s t 2 - 3rs 2 t
b)
4y 2 - 20y + 25
c)
36r 4s 3rs + 27 r 2
Solution
a)
r 2 s t 2 - 3rs 2 t

b)
c)

= r(rs t 2 - 3s 2 t)
take out the common factor r
= rs(r t 2 - 3st)
take out the common factor s
= rst(rt - 3s)
take out the common factor t
2
2
2
4y - 20y + 25 = (2y) - 2(2y)(5) + 5
form x 2 - 2xy + y 2
= (2y 5) 2
36r 4s 3rs + 27 r 2
= 36r + 27r 2 - 4s 3rs
Rearrange
expression
= 9r(4 + 3r) s(4 + 3r)
= (4 + 3r)(9r s)
take out the common factor (4 + 3r)

4. When factorizing and simplifying algebraic fractions,


- factorise the expansion
- eliminate the common factors
Example 4
Simplify the following
a)
- 28m 2 n 4mn
27 s 2 75
9 s 15

b)
Solution
a)

- 28m 2 n

4mn =

27 m 2 n
4mn
7

28 m m n
4 m n

= -7m
27 s 75
9 s 15
2

b)

3(9 s 2 25)
3(3s 5)

eliminate the common factor 3

(9 s 2 25)
(3s 5)
(3s 5)(3s 5)
=
(3s 5)

= 3s + 5

factorise the numerator and


eliminate the common factor

Adding and subtracting algebraic fractions


1. Similar denominator
I.
Maintain the denominator
II.
Add or subtract both the numerator
III.
Simplify
3x 5

Example: 2 y 3

6x 7

- 2y 3

=
=

3x 5 6 x 7
2y 3
3x 6 x 5 7
2y 3

= -3x + 2
2. Different denominators without common factors
I.
Multiply the numerator and denominator with the other denominator
II.
Add or subtract both the numerator
III.
Simplify, if possible
3b

Example: a

8
c

3b c

= a c

8a

- ca

3bc

= ac
=

8a
ca

3bc 8a
ac

3. Different denominators with having one common factor


I.
Find the LCM for both the denominators
II.
Change the algebraic fraction to equivalent fraction
III.
Add or subtract both the numerator
IV.
Simplify, if possible
Example:

2m 3
4n

6 3m
6n

( 2m 3) 3
4n 3

(6 3m) 2
6n 2

6m 9
12 6m
12n
12n
6m 9 12 6m
=
12n

12m 21
12 n

3( 4m 7)
3( 4n)
4m 7
=
4n

Multiplying algebraic fractions


1. Denominator with one term : multiply terms separately
x

Example: yz

x t

t
sy

= yz sy
=

xt
sy 2 z

Onewith
termtwo terms
2. Denominator
3( a b)

Example : a b

b a
a b

3( a b)
a b

= -3
Two terms
Dividing algebraic fractions
1. Denominator with one term : multiply terms separately
m

Example: 4n

c
2d

= 4n
dm

= 2cn
Onewith
termtwo terms
2. Denominator

2d
c

( a b)
a b

3x 1

Example : 3 x 21

x 5
4 x 28

3x 1

= 3 x 21

4 x 28
x 5

3x 1

Two terms

= 3( x 7)
12 x 4

= 3 x 15
Test yourself
1. Expand each of the following
a) (2x + 3)(2x 1)
b) (6 7p)
2. Factorise each of the following
a) 4a 2 + 18a
b) 9y 2 + 48yz + 64z 2
3. Simplify the following
a) (-120x 3 y) 30xy 3
b)

(a b) 2
a 2 b2

4. Solve the following


y z
2( y 2 z 2 )
5x
b) x 2 x

a)

4( y z )
3( y z )

x2 x
4( x 1)

4( x 7 )
x 5